2020
DOI: 10.1094/mpmi-01-20-0005-a
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Phytoplasma Strains Associated with Sugarcane Grassy Shoot (SCGS) and Bermuda Grass White Leaf (BGWL) Diseases

Abstract: We performed whole-genome sequencing of two phytoplasmas associated with sugarcane grassy shoot (SCGS) and Bermuda grass white leaf diseases. These are the first draft genomes of SCGS phytoplasma (strain SCGS) and ‘Candidatus Phytoplasma cynodontis’ (strain LW01) and may help to delineate these phytoplasmas at a finer taxonomic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The first complete genome of phytoplasma (onion yellows phytoplasma mild strain (OY-M) was published in 2004 [ 6 ] (data deposited into GenBank in 2003). So far, 47 phytoplasma genomes (35 draft and 12 complete) have been sequenced involving 13 groups and 29 subgroups ( Figure 2 and Table 1 , [ 6 , 7 , 14 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]). The size of the complete ge-nomes ranges from 576 to 960 Kb.…”
Section: Phytoplasma Nomenclature: Delineation Of Candidatu...mentioning
confidence: 99%
“…The first complete genome of phytoplasma (onion yellows phytoplasma mild strain (OY-M) was published in 2004 [ 6 ] (data deposited into GenBank in 2003). So far, 47 phytoplasma genomes (35 draft and 12 complete) have been sequenced involving 13 groups and 29 subgroups ( Figure 2 and Table 1 , [ 6 , 7 , 14 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]). The size of the complete ge-nomes ranges from 576 to 960 Kb.…”
Section: Phytoplasma Nomenclature: Delineation Of Candidatu...mentioning
confidence: 99%
“…Simultaneously, the enriched nucleic acids of SCGS and LW01 were sequenced on the ONT platform. The draft genome sequence of both the phytoplasma strains was obtained as described earlier [51]. The final SCGS assembly contained 29 scaffolds corresponding to 505 173 bp including a putative plasmid of 2976 bp.…”
Section: Full-textmentioning
confidence: 99%
“…All of these weed species except C. sparsiflora have been reported earlier as hosts of different phytoplasma groups (Rao et al 2017). C. bonplandianum has been reported as host of 16SrII and 16SrVI-D subgroup of phytoplasmas in India (Kirdat et al 2020), and we reported another species, C. sparsiflora as Fig. 8 Phylogenetic tree of secY gene sequences constructed by neighbor-joining method and Kimura's three-parameter model, showing the relationships among chickpea phytoplasma isolates, weed isolates and alternate host with reference phytoplasma strains.…”
Section: Discussionmentioning
confidence: 93%